Having Fun Counseling: Upaya Pemberdayaan Bagi Masyarakat di Kecamatan Pathuk, Gunung Kidul - Rara Eka Yurika; Muhsin Muhsin (Jurnal Relawan dan Pengabdian Masyarakat REDI, 2024)
Having fun counseling is a community service activity resulting from collaboration between lecturers, students and the community located in Gunung Ireng tourism, Pathuk District, Gunung Kidul. The purpose of having fun counseling is to create a fun climate for the community and students, to develop social and emotional skills, and build good social relationships as an effort to strengthen bonding relationships across all elements. Having fun counseling is carried out with four stages, namely observation, problem formulation, activity implementation, and outuput. The methods used in carrying out having fun counseling are consultation and mediation methods. Based on the results of the output analysis, it is stated that this activity has a positive impact on the community.